2021
DOI: 10.3389/fimmu.2021.686240
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma Markers of Disrupted Gut Permeability in Severe COVID-19 Patients

Abstract: A disruption of the crosstalk between the gut and the lung has been implicated as a driver of severity during respiratory-related diseases. Lung injury causes systemic inflammation, which disrupts gut barrier integrity, increasing the permeability to gut microbes and their products. This exacerbates inflammation, resulting in positive feedback. We aimed to test whether severe Coronavirus disease 2019 (COVID-19) is associated with markers of disrupted gut permeability. We applied a multi-omic systems biology ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 55 publications
10
102
1
2
Order By: Relevance
“…Our study further explores the effect UAU has on COVID-19 disease outcomes. Our findings are supported by prior studies that suggest that alcohol exposure may augment the activity of proinflammatory cytokines (interleukin 1β, interleukin 6, and tumor necrosis factor) in SARS-CoV-2 infection and cause pulmonary, gastrointestinal, hepatic, and neurologic organ dysfunction [15,16]. Another study demonstrated that alcohol causes severe oxidative stress due to the depletion of glutathione in the alveolar space, which leads to increased susceptibility to sepsis-mediated ARDS [17].…”
Section: Comparison With Prior Worksupporting
confidence: 89%
“…Our study further explores the effect UAU has on COVID-19 disease outcomes. Our findings are supported by prior studies that suggest that alcohol exposure may augment the activity of proinflammatory cytokines (interleukin 1β, interleukin 6, and tumor necrosis factor) in SARS-CoV-2 infection and cause pulmonary, gastrointestinal, hepatic, and neurologic organ dysfunction [15,16]. Another study demonstrated that alcohol causes severe oxidative stress due to the depletion of glutathione in the alveolar space, which leads to increased susceptibility to sepsis-mediated ARDS [17].…”
Section: Comparison With Prior Worksupporting
confidence: 89%
“…For example, Siendelar et al [36] found that a panel of 22 metabolites (including PC and LPC), predicted disease severity (as measured as need for ICU admission). Giron et al [38] reported that alterations in secondary bile acids levels, resulting from disrupted crosstalk between gut and lung, are associated with ICU admission. The reasons for these discrepancies are purely speculative.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Respiratory infections are known to cause gastrointestinal distress, dysbiosis, and increased intestinal permeability despite an absence of virus in the GI environment (135). SARS-CoV2 patients experience noted dysbiosis and loss of intestinal integrity corresponding with more severe systemic inflammation, bacteremia, and higher mortality ratepotentially signifying a leaky gut as a contributor to worsening disease outcomes (136,137). Additionally, human immunodeficiency virus (HIV) infection has been shown to cause systemic immune activation and AIDs-related morbidity due to translocation of bacteria from the intestinal lumen (138).…”
Section: Infection As An Instigator Of Intestinal Permeabilitymentioning
confidence: 99%